Polar bears past bedtime - Osborne, Mary Pope.; Murdocca, Sal (New York : Scholastic, 1998)
Their magic tree house takes Jack and Annie to the Arctic, where a polar bear leads them onto very thin ice.
"A Stepping Stone book."
"RL: 2.1"--Cover p. [4].
Keywords: Polar bear -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Polar bear -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Arctic regions -- Fiction; Arctic regions -- Juvenile fiction